Moving from EU-centrisms: Lessons from the Polycrisis for EU studies and Global South Regionalism - Sebastião, Dina (2023)
This article reflects on the responses to global crises in Global South regionalisms and the EU, emphasising the need for disrupting research agendas, strengthening disciplinary and theoretical diversity accounts in the EU and comparative regionalism studies in general. The article collects trends and challenges highlighted by the literature on EU and regionalism in Global South from 2008 onwards, aiming to address as main research question: how EU studies and Global South scholarship developed after multiple global crises to contribute to the theorisation renewal and the disruption of research agendas? Stemming from the concept of global polycrisis, two relevant and multidimensional crises are analysed: the 2008 global financial crisis and the migration influxes derived from humanitarian crises. By studying both the EU and Global South experiences, we aim to contribute to move beyond the Eurocentric foundations of the regionalism studies, emphasising that knowledge production needs to be more empirically sensitive to context and social reality.